Analysis of the Influence of Competency Development and Compensation Systems on Employee Performance: A Literature Study of Strategic Human Resource Management - Putra, Pramudita Syah; Laila, Dilla Apri; Hariyati, Hariyati; Aima, Havidz (Jurnal Penelitian Multidisiplin Bangsa, 2025)
This research analyzes the influence of competency development and compensation systems on employee performance through literature review approach within strategic human resource management perspective. Library research methodology was employed to synthesize findings from various scientific publications during 2020-2025 period. Analysis results demonstrate that competency development operates through cognitive, psychomotor, and affective dimensions forming employees' holistic capabilities. Compensation systems integrate financial and non-financial components within total reward framework influencing motivational dynamics. The interrelation between both variables creates synergistic effects strengthening performance outcomes through reinforcement mechanisms. Strategic implications indicate that systematic integration between competency development and compensation alignment generates sustainable competitive advantages. This research contributes to theoretical framework development in strategic HRM and provides insights for practitioners in optimizing human capital investments.